The effect of financial performance, tax avoidance, sales growth, and tax expense on capital structure - Lestari, Diah Ayu; Wadi, Indra (Educoretax, 2024)
This research aims to determine the effect of financial performance, tax avoidance, sales growth, and tax burden on capital structure. This type of research is quantitative. Capital structure is the dependent variable and financial performance, tax avoidance, sales growth and tax burden are independent variables. This research uses secondary data in the form of financial reports, with a population of 92 companies. This research was conducted on property and real estate sector manufacturing companies listed on the IDX in 2018-2022, the research sample was 13 companies with 5 years of observation, the sample determination method used was purposive sampling . The analysis method uses multiple regression analysis, determination test, T test and F test using Eviews 12. The research results show that tax avoidance has no effect on capital structure, sales growth has no effect on capital structure, and tax burden has no effect on capital structure, financial performance influence on capital structure. Meanwhile, financial performance, tax avoidance, sales growth and tax burden simultaneously influence capital structure.